Pengukuran Kinerja Organisasi Sektor Publik Dengan Metode Balanced Scorecard (Studi Kasus Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bandung Barat) - Sugianti, Lilis; Sembiring, Etti Ernita (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The aim of this study was to measure and analyze the performance of Population and Civil Registry Office in West Bandung District in a comprehensive manner using the balanced scorecard method. This study collected data from distributing questionnaires to the community as respondents and interviewing Population and Civil Registry Office of West Bandung District employees. This type of research is a qualitative quantitative research by analyzing data from the four balanced scorecard perspectives. The data sources used are primary and secondary data sources. Collecting data using the method of documentation, questionnaires, and interviews. The sampling technique used purposive sampling and random sampling. Performance measurement from a financial perspective uses a value for money. While each perspective is measured by the level of satisfaction and overall performance measurement is weighted score on each perspective using the Dally weighting technique. The results of this study indicate that: (1) The Financial Perspective has the quality of Very Economical, Inefficient, and Effective Performance. (2) Customer Perspective Has Satisfactory Performance Quality (3) Internal Business Process Perspective Has Satisfactory Performance Quality (4) Learning and Growth Perspective Has Satisfactory Performance Quality. So that the measurement of the performance measurement of the Population and Civil Registry Office of West Bandung District as a whole has good performance quality.